Gender: look right, look right - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Gender-Orientation in the Post Harvest Sector: Pointers for identifying Gender-Specific Aspects in the Post-Harvest Sector, By D Guenther, with E Zimprich. 1998. 36 pp. Available free in printed form from A Bell, GTZ OE 4541, Room 1615 GTZ, Postfac